KEPEMIMPINAN KEPALA SEKOLAH BERDASARKAN KECERDASAN EMOSIONAL (EQ) DI SMA NEGERI 1 SEPUTIH BANYAK TAHUN PELAJARAN 2024/2025 - Dewi Lestari; Agus Sujarwo; Garum (UNISAN JURNAL, 2025)
School principals play a crucial role in determining the direction, climate, and quality of educational institutions. This study explores the implementation of emotional intelligence (EQ)-based leadership by the principal of SMA Negeri 1 Seputih Banyak in the 2024/2025 academic year. Using a descriptive qualitative method through interviews, observation, and documentation, the research reveals that the principal consistently integrates the five dimensions of EQ—self-awareness, self-regulation, motivation, empathy, and social skills—into daily leadership practices. These emotional competencies positively influence communication, conflict resolution, teacher motivation, and school climate. The findings show that EQ-based leadership contributes significantly to building a harmonious, collaborative, and performance-driven school environment. The study concludes that the principal’s emotional intelligence not only enhances interpersonal relationships but also improves teacher effectiveness and overall school productivity.